An investigation of the aquatic macroinvertebrate fauna of the southern Great Escarpment (South Africa): insights from ecological and genetic studies - Taylor, Chantal Lee (Rhodes University, Faculty of Science, Botany Department, 2016)
Biological diversity in freshwater biomes is vital to maintain healthy, functioning ecosystems with resilience to disturbance and the impacts of climate change. Freshwater ecosystems provide essential resources to life on Earth. However, as increasing pressure is being placed on the environment by human population growth, the quality of freshwater resources and the health of these ecosystems are at risk. Mountain streams provide an important source of water and are usually less affected by anthropogenic stressors, compared to lowland freshwaters. These montane streams are therefore of important conservation value and due to their untransformed nature serve as ideal ecosystems for biodiversity studies and as reference sites for studies on environmental change. This study explores aquatic macroinvertebrate biodiversity of the southern Great Escarpment in South Africa. Species assemblages and the environmental variables of each site were sampled from first order streams across five different mountain blocks along the Great Escarpment. Additionally, mitochondrial DNA of three mayfly species (Afroptilum sudafricanum, Demoreptus natalensis and Demoreptus capensis), commonly occurring in the study area, was analysed to compare the genetic diversity between habitat specialist and habitat generalist species. A total of 2 595 macroinvertebrate specimens from 47 families and 86 species were collected with several interesting and potentially new species being discovered. Partitioned diversity analyses indicate that macroinvertebrate diversity varies across mountain blocks. Multivariate analyses indicate that differences in assemblages could be attributed to differences in environmental variables between sites, particularly water velocity, total dissolved solids and salinity. As these environmental variables reflect of the topography of the sites, differences in species assemblages was attributed to difference in topography and therefore biotopes present. Habitat-restricted mayfly species (D. natalensis and D. capensis), occur in distinct populations confined to mountains blocks. Isolation-by-distance analyses further emphasis that these species are genetically restricted by their habitat preference for mountain streams. In contrast, A. sudafricanum, a habitat generalist, showed no indication of genetic structure due to location or distance. Possible cryptic taxa and new species were identified within A. sudafricanum and Dermoreptus respectively. This study provides an important contribution to the baseline data of freshwater macroinvertebrate diversity for the southern Great Escarpment region and provides insights into the considerable genetic diversity of selected aquatic taxa across this region.
Keywords: Uncatalogued